2022
DOI: 10.28991/cej-2022-08-02-010
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced-concrete Bond with Brine and Olive Oil Mill Wastewater

Abstract: Since the interaction between the steel reinforcement and concrete directly controls the bond strength between them, poor bond performance results in a direct negative effect on the existing state of reinforced concrete structures. This bond is one of the most important factors affecting the strength of reinforced concrete. The bond strength is measured using the pull-out test. The present paper discusses the effect of the addition of brine and olive oil mill wastewaters to the reinforced concrete mixes. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
(34 reference statements)
2
10
0
Order By: Relevance
“…Previous research showed that the addition of olive oil mill and brine wastewaters significantly increased the compressive strength when compared to the reference mixtures and also showed that the best percentages that could be added were 7.5% and 10% of the olive oil mill and brine wastewater, respectively, which have been proven in this research [1][2][3][4].…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Previous research showed that the addition of olive oil mill and brine wastewaters significantly increased the compressive strength when compared to the reference mixtures and also showed that the best percentages that could be added were 7.5% and 10% of the olive oil mill and brine wastewater, respectively, which have been proven in this research [1][2][3][4].…”
Section: Introductionsupporting
confidence: 72%
“…Specifications, Chemical, and physical properties can be referred to in Alzgool et al [1], Alshboul et al [2], and Alzgool [3].…”
Section: Brine Wastewater Cement Olive Oil Mill Wastewater and Silica...mentioning
confidence: 99%
See 1 more Smart Citation
“…From an economic and environmental standpoint, waste creation and disposal is an issue of fundamental relevance for growth at the present moment, with direct consequences for sustainability [4][5][6]. To ensure that the concrete's resistance strength is not compromised, it is important to pay close attention to the ratios of its components while recycling materials into the material [7][8][9]. Previous research has shown this [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…If wet thermochemical extraction (WTE) and dry thermochemical extraction (DTE) are applied to treat biomass ( Bilen and Turan, 2022 ; Yang et al, 2018 ; Zhang et al, 2020 ), its lignin components can effectively be destroyed and generate a large amount of phenolic components, which are similar to phenolic disinfectants ( Déniel et al, 2017 ; Torri et al, 2012 ; Turan et al, 2019 ). Moreover, the liquid products from DTE process, usually called wood vinegar, has been used as disinfectant in the agriculture ( Alzgool et al, 2022 ; Gao et al, 2020 ; Ismail et al, 2022 ; Turan et al, 2022 ). Further, it was found that a high inactivation rate of pathogenic virus and bacteria by the bio-liquid from wet thermochemical extraction (WTE) ( Yu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%